Feminitas dan Resistansi Perempuan: Dekonstruksi Makna melalui Wacana Kritis Sara Mills dalam Film 'Mother' - Rhesa Zuhriya Pratiwi; Eny Susilowati; Joni Rusdiana; Arina Rohmatika (Muwazah, 2021)
The strength of film as a medium that represents and constructs reality with the storyline which is symbolically packaged, through substance and full of socio-cultural values. This study is to describe the deconstruction of femininity and women's resistance meaning in the â€œMotherâ€ movie. This research is a descriptive qualitative text research using main analysis of critical discourse by Sara Mills. The subject is the â€œMotherâ€ movie, a thriller drama directed by Bong Joon-Ho. Collecting data at the text level, especially through documentation and literature studies, and furthermore, data is validated through FGD with experts who have experience and knowledge according to the object of research. The results explain the deconstruction of feminine values and women's resistance meaning in the â€œMotherâ€ movie positioning women as objects. At this level, there is an objectification of women through the main character played by Hye ja, although another tendency appears which also positions women as subjects in the storyline. The emergence of physical and emotional aspects of femininity strengthens the objectification of women in the film. However, there is a dissection on femininity and resistance value in the film due to the emotional dynamics of the main characterâ€™s complex character. Finally, the existence of media as an industry and the power of messages makes the practice of media commodification depends on the owners, so itâ€™s possible that the image of the female character in the film is used to represent a form of media power over the commodification of the message conveyed.